Trypanorhynch cestode larvae parasitizing Hyporthodus niveatus (Valenciennes, 1828) (Actinopterygii) collected from fish markets in the municipality of Niterói, RJ, Brazil - Menezes, Priscila Queiroz Faria de; Fonseca, Michelle Cristie Gonçalves da; Gomes, Delir Corrêa; Torres, Eduardo José Lopes; São Clemente†, Sergio Carmona de; Knoff, Marcelo (Food Science and Technology, 2023)
This study is a continuation of the survey about helminths parasitizing the white grouper, Hyporthodus niveatus, a marine fish purchased from fish markets in the municipality of Niterói, Rio de Janeiro State, Brazil. Specifically, this study reports the results of an investigation concerning trypanorhynch cestodes parasitizing this host. A total of 20 fish specimens were caught by professional fishermen off the coast of Rio de Janeiro State. The fish were measured and necropsied, and their organs were investigated for trypanorhynch cestodes. A total of 13 H. niveatus were parasitized by 67 specimens of trypanorhynch cestode plerocerci that were found infecting the visceral serosa, stomach, intestine, and abdominal musculature. The taxonomic identification of these parasites was based on morphological and morphometric characters using bright-field and scanning electron microscopies. Five trypanorhynch species were identified: Pintneriella gymnorhynchoides, Grillotia (Christianella) carvajalregorum, Pterobothrium crassicolle, Callitetrarhynchus gracilis, and Callitetrarhynchus speciosus, and their parasitic indices were presented. This is the first report on the occurrence of P. gymnorhynchoides in the Western Atlantic Ocean. Apart from the repugnance, the presence of cestode plerocerci is worrisome because of the potential risk of allergic reactions, thereby reinforcing the hygienic-sanitary significance of monitoring these parasites.